Overcoming multidrug resistance in human lung cancer with novel benzo[a]quinolizin-4-ones - Yodsoi Kanintronkul (2018)
Aim: To investigate the ability of synthetic benzo[a]quinolizin-4-one derivatives to reverse multidrug resistance (MDR) in lung cancer cells. Materials and Methods: A cell line with MDR, A5 49RT-eto, was established by exposure to 1.5 μM etoposide. Cytotoxic activity was assayed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromine (MTT) method. The mechanism of drug resistance was studied by real-time PCR, Western blot analysis, and flow cytometry. Benzo[a] quinolizin-4-one derivatives were synthesized and tested for cytotoxic activity and ability to modulate MDR. Results: A549RT-eto cells had an IC 50 for etoposide of 176 μM, 28-fold higher than parental cells, due to increased levels of MDR1 gene and P-glycoprotein (P-gp), resulting in greater drug efflux. Three benzo[a]quinolizin-4-ones reduced etoposide IC 50 from 176 μM to 22.4 μM -24.7 μM. This resulted from increased drug accumulation without altering P-gp expression at the transcription or translation level. Conclusion: Non-toxic concentrations of benzo[a]quinolizin-4-one derivatives can reverse drug resistance of A549RT-eto by increasing the intracellular drug accumulation.